EVALUATION OF ATHLETES’ NUTRITIONAL NEEDS IN UNIVERSITY OF ILORIN, ILORIN KWARA STATE - Gboyega Aladesusi (Universitas Teknokrat Indonesia, 2022)
ABSTRACTThis study evaluated of athlete’s nutritional needs for sports performance among athletes in University of Ilorin, Kwara state. The population consisted of 500 athletes of University of Ilorin while the sample included 54% of athletes that have represented the University of Ilorin in one or two games. A simple random sampling was used to select respondents and a total of one hundred (100) respondents were used, a researcher structure questionnaire was adopted and the reliability was also ascertained. The objectives of this study were to find out how nutrition, muscular strength, weight, endurance level and body flexibility contributes to sport performance among athletes. The data collected was analyzed using Pearson Product Moment Correlation Co-efficient at 0.05 alpha level. The finding of the study revealed that nutrition, muscular strength, weight of the body, level of endurance and body flexibility of the athletes contributed to their performance in sport. It was therefore recommended among others that athletes should adopt nutrition strategies, strength training, endurance training and the flexibility training that will optimize physical performance and support good health which will lead to enhanced performance in sport and reduce the risk of illness and injury.